2020
DOI: 10.1038/s41598-020-62711-7
|View full text |Cite
|
Sign up to set email alerts
|

GWAS revealed a novel resistance locus on chromosome 4D for the quarantine disease Karnal bunt in diverse wheat pre-breeding germplasm

Abstract: This study was initiated to identify genomic regions conferring resistance to Karnal Bunt (KB) disease in wheat through a genome-wide association study (GWAS) on a set of 179 pre-breeding lines (PBLs). A GWAS of 6,382 high-quality DArTseq SNPs revealed 15 significant SNPs (P-value <10 −3) on chromosomes 2D, 3B, 4D and 7B that were associated with KB resistance in individual years. In particular, two SNPs (chromosome 4D) had the maximum R 2 values: SNP 1114200 | F | 0-63:T > c at 1.571 cM and R 2 of 12.49% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This data warrants a thorough scan of the D-genome by including the T. aestivum lines originating from diverse geographies in the panel to have an idea about the diversity and evolution of KB resistance. Recently, Singh S. et al (2020) reported two candidate gene hits on chromosome 4D that substantiate the hypothesis that the wheat genome and particularly the D-genome has a high potentiality of harboring KB resistance genes. It can be assumed that the non-pleiotropic KB resistance genes had not been favored by natural selection, in the global genotypes, because of the absence of the pathogen.…”
Section: Genetics Of Kb-free Traitmentioning
confidence: 62%
See 3 more Smart Citations
“…This data warrants a thorough scan of the D-genome by including the T. aestivum lines originating from diverse geographies in the panel to have an idea about the diversity and evolution of KB resistance. Recently, Singh S. et al (2020) reported two candidate gene hits on chromosome 4D that substantiate the hypothesis that the wheat genome and particularly the D-genome has a high potentiality of harboring KB resistance genes. It can be assumed that the non-pleiotropic KB resistance genes had not been favored by natural selection, in the global genotypes, because of the absence of the pathogen.…”
Section: Genetics Of Kb-free Traitmentioning
confidence: 62%
“…This agronomically minor but quarantine major disease is a major hindrance to wheat cultivation, production, and movement from the areas of its endemism. Therefore, it is of paramount importance that wheat breeding programs in the affected and vulnerable countries augment the efforts toward the identification and development of resistant sources ( Singh S. et al, 2020 ). In spite of the high economic importance of KB, unfortunately, resistance breeding targeting KB has never been given much priority compared to other fungal diseases of wheat like rusts and Fusarium head blight possibly owing to geographical confinement of the disease to a few countries or low direct yield loss that mostly stands between 1% and only in rare cases up to 20% to 40% ( Vocke et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Seeds of Discovery (SeeD) project at CIMMYT has resulted in the creation of new pre-breeding germplasm with a view to enhance the use of genetic resources in breeding programs (Singh et al 2018). The same germplasm has been used to track loci linked to yield-related traits (Akram et al 2020), nematode resistance (Dababat et al 2021), karnal bunt (Singh et al 2020) and terminal drought stress (Shokat et al 2020a). However, determining the genetic basis of physiological traits has not been attempted so far.…”
Section: Introductionmentioning
confidence: 99%